Pengaruh Penerapan Pendidikan Agama Kristen Terhadap Penanaman Nilai Kesabaran Anak Usia 4-6 Tahun Di TK Elfrida Harder HKBP Siborongborong (Sekolah Tinggi Agama Buddha Nalanda, 2023)
The aim of this research is to determine the effect of implementing Christian Religious Education on the value of cultivating patience in children aged 4-6 years at Elfrida Harder Kindergarten HKBP Siborongborong. The research method used is a quantitative descriptive research method. The population is all group B students (aged 4-6 years) at Kindergarten Elfrida Harder HKBP Siborongborong totaling 35 people. Data collected using a positive closed questionnaire consisted of 10 items for variable Test analysis requirements: a) test the relationship that obtains a positive value rxy = 0,568 > rtabel(α=0,05,n=35) = 0,334. b) A significant relationship test is obtained thitung= 3,967 > ttabel(α =0,05,dk=n-2=33)= 2,042. 2) Influence test: a) Test the regression equation, obtain the regression equation . b) Regression coefficient of determination test (r2) = 32.3%. 3) Test the hypothesis using the F test to obtain Fhitung > Ftabel=( α =0,05,dk pembilang k=12,dk penyebut=n-2=35-2=33) namely 15.73 > 2.09. Thus Ha, that is, there is an influence of the application of Christian Religious Education on instilling the value of patience in children aged 4-6 years at TK Elfrida Harder HKBP Siborongborong is accepted and H0 is rejected.